Toward Eradication of Hepatitis C Infection Among Immigrants to Canada - Mortazhejri, Sameh (Université d'Ottawa / University of Ottawa, 2025)
Background: Canada has adopted the World Health Organization’s targets to eliminate hepatitis C (HCV) as a public health threat by 2030. Despite the availability of effective screening and treatment, uptake in Canada remains suboptimal. Immigrants from HCV endemic countries account for 35% of cases in Canada, with an average 10-year delay in diagnosis, leading to poorer health outcomes and increased healthcare system costs. This research explored barriers and enablers to HCV screening and treatment among immigrants from the perspectives of both immigrants and healthcare providers. Methods: I conducted three theory-informed qualitative descriptive studies using semi-structured interviews. The first two studies focused on Egyptian immigrants in Ottawa and Punjabi immigrants in Montreal. Two Community Advisory Groups familiar with the respective communities provided input throughout the research process. I applied the Common-Sense Self-Regulation Model and the Theoretical Domains Framework (TDF) to explore perceptions of HCV and the barriers and enablers to care. The third study applied the TDF to examine healthcare providers’ perspectives on delivering HCV care to immigrants in both cities. All interviews were double-coded using the relevant frameworks, and key findings were identified. Results: I conducted interviews with 34 immigrants (18 Egyptian and 16 Punjabi) and 12 healthcare providers. Punjabi immigrants demonstrated lower awareness of HCV and greater language-related barriers, often relying on family or community members. Egyptian participants had higher awareness and fewer language challenges. Despite these differences, both groups identified the asymptomatic nature of HCV, fear, and stigma as key barriers. Long wait times and shortages of family physicians were reported by both immigrants and providers. Providers also highlighted additional barriers, including the absence of standardized immigrant-specific guidelines, limited training in HCV care, time constraints, and fragmented services. Nonetheless, immigrant participants expressed a strong willingness to engage in care if diagnosed. Conclusion: This research identified individual, provider, and system-level barriers to HCV care among immigrants in Canada. While shared challenges exist, community-specific differences underscore the need for culturally tailored and multilevel strategies. Findings can inform theory-based implementation and policy efforts to improve timely and equitable HCV care access for immigrant populations.
Keywords: Hepatitis C; Barriers; Qualitative research; Immigrants; Implementation science; Theoretical Domains Framework; Common-Sense Self-Regulation Model